Constructive alignment of assessment practices in English language classrooms - Genon, Lynrose Jane Dumandan; Torres, Chezka Bianca P. (English Language Teaching Educational Journal, 2020)
This qualitative study identified the language assessment practices in terms of purpose, type, and timing in four elementary language classes in the Philippines. It then evaluated the constructive alignment and content validity of the assessment and described how the constructive alignment reflects the quality of teaching and learning in these language classrooms. Findings revealed that the assessment practices are entrenched in the teachers’ pedagogy serving various purposes (like monitoring, facilitation and motivation) other than evaluation.   Generally, the assessment content and tasks show alignment to targeted learning goals. Several assessments, however, do not target the intended skill but rather tapped on the sub-skill, and they reveal alignment issues as well as teaching-learning conditions in the classrooms. Findings uncover, albeit a snapshot, of the gaps not only in assessment practices, but also in the articulation of curriculum goals leaving teachers to interpret and operationalize these on their own. These issues affect the students’ achievement since alignment affects achievement and opportunity to learn is at optimum levels when lesson plans are aligned with benchmarks, standards, and assessments, thus increasing academic achievement.